Algae-Derived Marine Oligosaccharides and Their Biological Applications - Jutur, Pannaga P.; Nesamma, Asha A.; Shaikh, Kashif M. (Frontiers in Marine Science, 2016)
The biological relevance of algae-derived marine oligosaccharides has potential significance in numerous applications of industrial biotechnology. Marine oligosaccharides are produced in algae naturally and/or by hydrolysis of derived polysaccharides. The potential of marine oligosaccharides is still unexplored, and these molecules, including their derivatives, are a versatile source of chemical diversity. In-depth knowledge on such molecules will provide novel insights, thus depicting their role in discovering mechanisms and the molecular functions within specific biological applications.